Complementary use of pulsed and continuous wave emission modes to stabilize melt pool geometry in laser powder bed fusion. (May 2019) - Demir, Ali Gökhan; Mazzoleni, Luca; Caprio, Leonardo; Pacher, Matteo; Previtali, Barbara
Graphical abstract: Highlights: The influence of CW and PW emission on melt pool geometry in LPBF was studied. The influence of scan geometry was evaluated with bulky and thin sections. Melt pool size was measured through coaxial monitoring with NIR images. Pseudo-tomographic 3D melt pool maps were constructed. Mixed CW/PW emission mode provides a more homogenous melt pool area over the build. Abstract: The most common defects in laser powder bed fusion (LPBF) namely porosity, geometrical errors, roughness and thermal deformations are principally linked with the energy input to the process. In common practice, a single set of process parameters is used to produce a whole component independently from the dimensions of the actual scan path within a given layer. However, melt pool stability is highly dependent on the scanned geometry. A possible strategy to maintain a constant melt pool is the mixed use of pulsed wave (PW) and continuous wave (CW) emission regimes. Accordingly, this work investigates the complementary use of continuous and modulated emission at fixed energy density on large and thin sections respectively. The proposed approach is tested on AISI 316L stainless steel and melt pool observations are conducted employing a coaxial monitoring system built for purpose. Temporally resolved measurements of intensity and geometrical properties of the melt pool were extracted as well as a three-dimensional spatial mapping of the molten pool area. The results demonstrate that moving from CW to a PW regime at the transition zones to thinner sections is effective in maintaining a constant melt pool size thus avoiding heat build-up and part extrusion from the powder bed.